PENERAPAN PENILAIAN KINERJA DALAM UPAYA MENINGKATKAN KEPUASAN KERJA KARYAWAN STUDI KASUS PADA PT INDOCEMENT TUNGGAL PRAKARSA TBK - Pramana Saputra; Dodi Wirawan (Jurnal Ilmiah Mahasiswa FEB, 2013)
The research aims to determine the procedures for application of performance appraisal in PTIndocement, current employees satisfaction and factors that influence the employeessatisfaction in the application performance appraisal. By using the methods of qualitativeresearch and case study approach in order to explore deeper picture about condition of theresearch subject and object. As the result from interpretation of the interview note that whenand how long the performance appraisal execute, who’s the judge and who’s be judge, whichmethods used, what kind of reward and punishment is given and like what forms forperformance appraisal. Furhermore, the condition of PT Indocement employees satisfaction isreally depend on the category of obtained scores as it will determine whether the employeegets a reward or punishment, and in assessing, the appraiser is often biase either intentionallyor not to maintain good relation between them. Cause good relation between employee andits supervisor are also included in one of the factors of employees satisfaction due toperformance appraisal.Keywords: Performance Appraisal, Employee Satisfaction.